Rancang Bangun Sistem Monitoring Cryptocurrency Secara Real Time Menggunakan Arduino - Edy suwasono (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Cryptocurrency is a blockchain-based technology that is often used today as a digital currency. This form of cryptocurrency is in demand by the public because of its decentralized management, easy process, and allows transactions without the need for third party intermediaries. Internet of things (IoT) technology has had a major influence on the development of information obtained to directly monitor changes in information without requiring human-to-human or human-to-computer interactions, such as displaying the stability of cryptocurrency, especially on Bitcoin, Ethereum, and Binance. This study aims to monitor data in real time using the Thingspeak.com application, the Arduino IDE as a data processor, and the real time data transmission line utilizing the ESP8266 module. The implementation results of the processed data are displayed on the OLED screen.